67 Gold standards framework implementation dudley group NHS foundation trust. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Bowen, Joanne; Hall, Kate; Lewis, Karen
Abstract : Gold Standards Framework (GSF) is a systematic, evidence based approach to optimise care for all patients approaching the end of life, delivered by generalist frontline care providers. There is evidence that 30% of adult hospital inpatients are in the last year of life (Clarke et al. 2014). The specialist palliative care team have completed a yearly audit to establish the percentage of adult inpatients on a particular date in June, who died during the following 12 months. The overall percentage is 33 percent of adult inpatients on the 3rd June 2018 had died within 1 year. Therefore, this data supported the published evidence and also supported the wards with the GSF implementation programme. Over the last 2 years the wards have engaged with six workshops and developed care plans based on national documentation for Gold Standards Framework Green, Amber and Red. The front runner wards '' elderly care, stroke and CCU have completed the requirements for accreditation and have been awarded GSF accreditation in August 2020. CCU is the first in the country to be GSF accredited. The improvements across these wards include the following which we were able to demonstrate through a GSF log data collection system: Increasing recognition of patients in the last year of life Increasing number of these patients offered advance care planning Increasing number of dying patients supported with Priorities for care of the dying person communication document Reduced length of stay for fast track patients The wards requested that the recording of GSF was available via the EPR system which has been achieved thanks to support from IT and allows staff to view patients that have been identified as GSF and if they have had an advance care plan offer or priorities for care communication document commenced. Furthermore, when a patient is re-admitted their previous GSF status will be visible on the tracking board. We are also able to record preferred place of death with documents on the EPR and are currently working with IT to enable reporting of achievement of preferred place on discharge and death. March - April 2020 as we all know have been unprecedented times with COVID-19. Our data offers assurance that the GSF has continued to be embedded across the hospital and patients are being identified as GSF which will include the use of appropriate care plans and enable the development of an individual plan of care. We have also demonstrated increasing number of patients identified for GSF and died on the wards with a reduction in the number of MET calls.